Shariah Fintech: An Analysis of Twitter Sentiment - Aisyah As-Salafiyah; Aam Slamet Rusydiana (SMART Insight, 2022)
This research was conducted to review the perception of sharia fintech within the scope of the sharia economy from the perspective of sentiment research on Twitter social media users in response to the development of sharia fintech. The method used in this study is a qualitative approach with descriptive statistics from the literature study in the form of 2131 Twitter tweets. A Python library software called VADER (Valence Aware Dictionary and Sentiment Reasoner) is used to classify tweets. Sentiment analysis results tend to perceive neutral sentiment at 80.8%, positive sentiment at 16.2%, and negative sentiment at 3.0%. The diversity of sentiment results shows that there are pros and cons to the development of sharia fintech. The benefits of this research are literature and considerations related to the development of sharia fintech and efforts to identify weaknesses and threats in the form of negative perceptions of the implementation of sharia fintech. In addition, to find out positive perceptions, strengths, potential, and benefits of Islamic fintech. This research is the first comprehensive study to discuss sentiment analysis on sharia fintech themes with Twitter tweet data. Suggestions for further research and recommendations are listed.